Xyphyre Enterprise: butter stick / Siti Nurismahani Razali [et al.] - Razali, Siti Nurismahani; Mohd Azman, Nazurah; Zuelhaidaan, Nazzira; Azizan, Noor Syazwani; Mohd Sazali, Farah Nur Izzati (2016)
Butter stick will be very helpful to our community due to the size that make it portable, easy to use and easy to keep. The easy way of the usage will make the users' chores become much easier.